Study of new eco-core metal matrix composite sandwich structure - Halim, Zahurin; Ahmad, Zuraida; Samat, Noorasikin; Anuar, Hazleen (2011)
The introduction of the eco-core sandwich panel composite is contributing a new approach to the designer to achieve high performance and light weight. These advanced natural fibre reinforced composite materials are increasingly being used in many applications including structural, aerospace, and defense and household appliances. However, the practical application for commercial use is not so widespread. High manufacturing cost can be justified if the product life cycle of the component is increased. Efforts have therefore been directed in recent years towards the development of suitable light-weight materials for many engineering applications and polymer matrix composites (PMCs) with phenolic or aluminium foam laminated composite have shown great promise in order to fulfill the current demands for structural applications. These materials in generally showed lower density and higher strength-stiffness ratios as compared to the conventional sheet metal or metallic materials and are expected to result in weight reduction of up to 50-60. However, no information is available in the literature on the study of eco-core metal matrix composite sandwich structure. In this research project, the new kenaf eco-core sandwich panel will be developed and then laminated with aluminium for the development of new advanced composite with the aim to investigate the effects of sandwich panel shape and variable metal faces on the properties of developed composites. The final goal is to find the optimum eco-core metal matrix composite sandwich structure with maximum mechanical properties such as stiffness and buckling. Kenaf eco-core sandwich will be fabricated and study on the interaction between eco-core sandwich panel and metal faces will be performed.